INTEGRATION OF LITHUANIAN INNOVATIVE NETWORKS INTO THE EUROPEAN RESEARCH AREA: A LOOK INTO THE PERSONAL NETWORKING FROM THE INSIDE AND THE OUTSIDE - Žvinklienė, Alina (Sociologija. Mintis ir veiksmas, 2015)
The basic principles of a personal networking may reflect on the perspectives of integration of Lithuanian innovative networks in the European Research Area from a sociological outlook. For this reason, Lithuanian and Swiss researchers’ national and international experience in the personal networking is analyzed using the social network analysis as a way of looking at a problem. It is meaningfully to say that institutional and inter-institutional relations and networked individualism as well should matter for the process of the personal networking. However, quality of the personal network is ensured only by personalized and direct communication. Therefore, any innovative network is rather a formal organization if the permanent, direct and personalized communication between the different institutional actors of the network is absent.